Shenkang injection for the treatment of acute kidney injury: a systematic review and meta-analysis - Shengchun Liao; Yurou Chen; Shuting Wang; Chen Wang; Chaoyang Ye (Renal Failure)
Objective Shenkang injection (SKI) has been widely used in China for many years for the treatment of kidney disease. The objective of this systematic review was to assess the efficacy of Shenkang injection for the treatment of acute kidney injury (AKI).Methods A search was conducted across seven databases, encompassing data from the inception of each database through October 8th, 2023. Randomized controlled trials comparing SKI-treated AKI patients with control subjects were extracted. The main outcome measure was serum creatinine (SCr) levels. Secondary outcomes included blood urea nitrogen (BUN), serum cystatin C (CysC), 24-h urine protein (24 h-Upro) levels, APACHE II score and adverse reactions.Results This meta-analysis included eleven studies, and the analysis indicated that, compared with the control group, SKI significantly decreased SCr [WMD = −23.31, 95% CI (-28.06, −18.57); p < 0.001]; BUN [WMD = −2.07, 95% CI (-2.56, −1.57); p < 0.001]; CysC [WMD = −0.55, 95% CI (-0.78, −0.32), p < 0.001]; 24-h urine protein [WMD = −0.43, 95% CI (-0.53, −0.34), p < 0.001]; and the APACHE II score [WMD = −3.07, 95% CI (-3.67, −2.48), p < 0.001]. There was no difference in adverse reactions between the SKI group and the control group [RR = 1.32, 95% CI (0.66, 2.63), p = 0.431].Conclusion The use of SKI in AKI patients may reduce SCr, BUN, CysC, 24-h Upro levels, and APACHE II scores in AKI patients. The incidence of adverse reactions did not differ from that in the control group. Additional rigorous clinical trials will be necessary in the future to thoroughly evaluate and establish the effectiveness of SKI in the treatment of AKI.